2021
DOI: 10.1016/j.jjimei.2021.100011
|View full text |Cite
|
Sign up to set email alerts
|

i-Pulse: A NLP based novel approach for employee engagement in logistics organization

Abstract: Although most logistics and freight forwarding organizations, in one way or another, claim to have core values. The engagement of employees is a vast structure that affects almost every part of the company's core environmental values. There is little theoretical knowledge about the relationship between firms and the engagement of employees. Based on research literature, this paper aims to provide a novel approach for insight around employee engagement in a logistics organization by implementing deep natural la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Operational performance is viewed as a key indicator in the supply chain management literature. Extant research has shown that operational performance depends on a number of antecedents, such as governance modes (Cao and Lumineau, 2015), the extent of collaboration (Chen, Preston and Xia, 2013), the successful implementation of ISO certifications (Lafuente, Bayo-Moriones and García-Cestona, 2010), the use of digital or other artificial intelligence-aided software (Chang and Gurbaxani, 2012;Deepu and Ravi, 2021;Garg et al, 2021;Kar, 2014) and other organizational factors (Um and Oh, 2020). Recently, research has been investigating the determinants of operational performance in the context of dyadic (Kar and Pani, 2014), triadic (Choi and Wu, 2009) and other multi-party relationships (Thomas et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Operational performance is viewed as a key indicator in the supply chain management literature. Extant research has shown that operational performance depends on a number of antecedents, such as governance modes (Cao and Lumineau, 2015), the extent of collaboration (Chen, Preston and Xia, 2013), the successful implementation of ISO certifications (Lafuente, Bayo-Moriones and García-Cestona, 2010), the use of digital or other artificial intelligence-aided software (Chang and Gurbaxani, 2012;Deepu and Ravi, 2021;Garg et al, 2021;Kar, 2014) and other organizational factors (Um and Oh, 2020). Recently, research has been investigating the determinants of operational performance in the context of dyadic (Kar and Pani, 2014), triadic (Choi and Wu, 2009) and other multi-party relationships (Thomas et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study discusses work engagement as variable mediation among role work systems and commitment. Deep psychology companies must give perspective to wellbeing to employee engagement (Garg et al, 2021). Pressure psychology in work can be reduced with work engagement with a training program (Jindo et al, 2020;Maltseva, 2020).…”
Section: ) Citationmentioning
confidence: 99%
“…Furthermore, work engagement is also related with system work (Maltseva, 2020). System work will help the work engagement process (Garg et al, 2021).…”
Section: ) Citationmentioning
confidence: 99%
“…This need gap requires developments from the processing of natural languages and machine learning. The Machine Learning (ML) and NLP algorithms can quickly transform large numbers of unstructured text into workable insights (Garg et al, 2021c). Natural language technologies have gained substantial focus from business, academia, and government since their inception.…”
Section: Motivation Behind Nlp In Logistics Trackingmentioning
confidence: 99%